Pemanfaatan Eco-Enzyme untuk Sanitasi Kandang dalam Pemeliharaan Kambing di Kelompok Tani Teman Abadi Kelurahan Mudung Laut Kota Jambi: Utilization of Eco-Enzyme for Pen Sanitation in Goat Farming in the Teman Abadi Farmers Group, Mudung Laut Village, Jambi City - Mairizal, Mairizal; Yusrizal, Yusrizal; Akmal, Akmal; Adriani, Adriani; Fahmida, Fahmida (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Teman Abadi Farmers Group is one of the farmer groups in Jambi City. Some members of the farmer group have a goat farming business with a semi-intensive maintenance system with semi-permanent pen buildings. Members of the farmer group have implemented pen sanitation but still use chemicals that can have other impacts on the health of livestock and farmers. Therefore, a solution was sought by utilizing natural disinfectants that are safe for livestock and humans, namely, eco enzymes. This Community Service Activity (PPM) is a form of knowledge and skills transfer to overcome the problem of implementing pen sanitation based on the use of eco-enzymes. This PPM activity uses the Participatory Rural Appraisal (PRA) method, which actively involves the community through focus group discussions (FGD), counseling, mentoring, and the practice of making eco enzymes as natural disinfectants. The evaluation was conducted by distributing questionnaires to determine the perceptions of farmer group members towards the implementation of PPM activities. PPM. The results of the activity showed that there was an increase in knowledge of farmer group members about the manufacture and use of eco enzyme as a disinfectant for cage sanitation. It was concluded that members of the Teman Abadi farmer group in Mudung Laut sub-district, Jambi City, already understand and practice using eco enzyme as a disinfectant for cage sanitation.